Anion Sensing by Solution‐ and Surface‐Assembled Osmium(II) Bipyridyl Rotaxanes. Issue 47 (14th October 2013) - Lehr, Joshua; Lang, Thomas; Blackburn, Octavia A.; Barendt, Timothy A.; Faulkner, Stephen; Davis, Jason J.; Beer, Paul D.
Abstract We report the preparation of [2]rotaxanes containing an electrochemically and optically active osmium(II) bipyridyl macrocyclic component mechanically bonded with cationic pyridinium axles. Such interlocked host systems are demonstrated to recognise and sense anionic guest species as shown by 1H NMR, luminescence and electrochemical studies. The rotaxanes can be surface assembled on to gold electrodes through anion templation under click copper(I)‐catalysed Huisgen cycloaddition conditions to form rotaxane molecular films, which, after template removal, respond electrochemically and selectively to chloride.